Discovery of novel BTK inhibitors with carboxylic acids. Issue 6 (15th March 2017) - Gao, Xiaolei; Wang, James; Liu, Jian; Guiadeen, Deodial; Krikorian, Arto; Boga, Sobhana Babu; Alhassan, Abdul-Basit; Selyutin, Oleg; Yu, Wensheng; Yu, Younong; Anand, Rajan; Liu, Shilan; et al.
Graphical abstract: Abstract: We report the design and synthesis of a series of novel Bruton's Tyrosine Kinase (BTK) inhibitors with a carboxylic acid moiety in the ribose pocket. This series of compounds has demonstrated much improved off-target selectivities including adenosine uptake (AdU) inhibition compared to the piperidine amide series. Optimization of the initial lead compound4 based on BTK enzyme inhibition, and human peripheral blood mononuclear cell (hPBMC) and human whole blood (hWB) activity led to the discovery of compound40, with potent BTK inhibition, reduced off target activities, as well as favorable pharmacokinetic profile in both rat and dog.